EKSPLORASI JENIS REPTIL DI SUAKA MARGASATWA TANJUNG SANTIGI KABUPATEN PARIGI MOUTONG - Putra, Adan Rizkya; Sudhartono, Arief; Ramlah, Sitti (Jurnal Warta Rimba, 2017)
Indonesia is a country that rich of natural resources which one of them is fauna. The variety of fauna is one of the certain natural wealth of Indonesia. Yet human characterisic to destroy forest has inflicted a loss. Therefore the fauna in its real habitat needs more attention so  it may become a media in conserving the fauna and the habitat in order to save it for the future generation. Means and infrastructure that can help to preserve the existing fauna are either conservation area, fauna rehabilitation or fauna park. The research was conducted in wildlife reserve of Tanjung Santigi in Santigi Village Ongka Malino Subdistrict Parigi Moutong District. The research was done for 3 month from August untill Oktober 2015, with observation period began at 06.00 up to 09.00 in the morning and obserbvation began at 16.00 – 18.00  in the afternoon. The technique of data gathering was done by using transect path and interviewing people around Wildlife Reserve of Tanjung Santigi, the observation on the location was done by following direction and  position of transect diameter slowly and at the same time making note of any reptile species found. The observation way was 3000 meter lenght with 50 meter lenght of left and right side. The data analysis consisted of species composition, evenness index and variety index. The result of the research that was done in wildlife resrve of  Tanjung Santigishowed that there were 5 reptile species found with the number of individual 48 that consisted of lizard (Cryptoblepharus novaeguinaeae), monitor lizard  (Varanus indicus), black snake (Ramphotyphlopsbraminus), small lizard (Hemidactylus frenatu), and house lizard (Gecko-gecko). The number of the reptiles found was affected by some factors, they were  effort  that was done in finding reptile. The effort counting was based on the time needed in searching in the location and the width of surveied area. Based on te result, it was found that on observation track that the variety index in the Wildlife Reserve area of Tanjung Santigi was low enough with H'=1,036.Keywords: Exploration of Reptile Species, Variety, Evenness, Wildlife Reserve of Tanjung Santigi.